First Five Year Plan Bombay State Panchmahals District - Government of Bombay (Government of Bombay, 1954)
The First Five-Year Plan (1951-56) for Panchmahals District in Bombay State presents a comprehensive framework for socio-economic development, targeting agriculture, education, health, and rural welfare. Agricultural initiatives emphasized irrigation improvements through wells and tank repairs, soil fertility enhancement via manure distribution, and expansion of agricultural colleges and schools to boost productivity. Veterinary and animal husbandry services were strengthened through dispensaries, vaccine production, and research on livestock improvement. Forestry management included afforestation and better administrative structures, while the Sarvodaya program promoted holistic rural development in education, health, and agriculture. Education initiatives encompassed school expansion, teacher training, and adult literacy programs, whereas healthcare improvements focused on hospitals, mobile dispensaries, preventive measures, and safe water supply schemes. Infrastructure projects prioritized road construction and nationalization of transport for improved connectivity. Economic measures supported cottage industries and backward classes through loans, subsidies, and cooperative efforts. Special attention was given to backward classes via scholarships, free education, financial aid, minimum wage protections, housing support, and cooperative development for artisans and laborers. The Community Development Programme further integrated local participation in agriculture, health, education, sanitation, and infrastructure projects, with pilot initiatives in Kalol Taluka demonstrating measurable outcomes. Overall, the plan reflects an inclusive, multi-sectoral strategy, aligning state objectives with local needs, promoting social equity, and fostering sustainable development through community involvement and targeted economic, educational, and health interventions.
Panchmahals District
Panchmahals District
Keywords: Panchmahals District; Five-Year Plan; Agricultural Development; Irrigation Projects; Veterinary Services; Education Initiatives; Adult Literacy; Health Services; Rural Development; Backward Classes; Community Development; Cottage Industries